FAKTOR RISIKO TERJADINYA GIZI KURANG PADA BALITA USIA 12-59 BULAN DI DESA BAWODOBARA KECAMATAN TELUKDALAM KABUPATEN NIAS SELATAN - Helda Sumawita Gowasa; Athira Demitri; Eka Nenni Jairani (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Toddlers are children aged 12-59 months, this period is characterized by a very rapid growth and development process and is accompanied by changes that require greater amounts of nutrients. The impact of malnutrition is very complex, children can experience problems with mental, social, cognitive and growth development. This research was to determine the risk factors for malnutrition in toddlers aged 12-59 months in Bawodobara Village, Telukdalam District, South Nias Regency. This research uses an analytical observational method with a case control approach. The population of this study were all toddlers aged 12-59 months, the sample size in this study used a ratio of 1:1. The sample size was 64 toddlers, consisting of the case group, which was malnourished, 32 toddlers and the control group, which was not malnourished, 32 toddlers. The sample was taken using a purposive sampling method with the chi square test and odds ratio. Research shows that there is a risk of maternal knowledge in the incidence of malnutrition in toddlers with p-value = 0.018 < 0.05 and OR 4.333, family income p-value = 0.001 < 0.05 and OR 11.667, history of infectious disease p-value = 0.002 < 0.05 and OR 6.943, and food intake p-value = 0.000 < 0.05 and OR 81,000. It is suggested that it is necessary to strive to increase knowledge about nutrition for toddlers by health workers by providing outreach such as distributing leaflets or brochures and using media such as providing shows about the importance of nutrition for toddlers to prevent malnourished toddlers.